Assessing species occurrence and species‐specific use patterns of bais (forest clearings) in Central Africa with camera traps. (20th May 2013) - Gessner, Julia; Buchwald, Rainer; Wittemyer, George
Abstract The impacts of increasing resource extraction on biodiversity in the Central African rainforest are largely unknown, in part due to the lack of baseline data on species occurrence across the basin. Natural forest clearings (bais) in this region are key habitats for a variety of vertebrates and offer opportunities for monitoring species distribution. Information on species composition, however, is lacking from the majority of areas (except for long‐term study sites). Approaches and protocols for short‐term bai assessments can greatly advance such baseline knowledge. This study demonstrates that camera traps provide an effective method for species inventories (species occurrence and temporal activity patterns) and monitoring at bais across the broader region. In comparison with direct observational studies, they performed especially well regarding rare and nocturnal species. Camera traps during sampling sessions of 4 weeks or less recorded previously undocumented, and 65–94% of the mammals known to use each of seven Central African bais. Results indicate that many mammal species, in particular African forest elephants (Loxodonta africana cyclotis), visit bais preferentially at night. This underlines the urgent need for monitoring tools providing both diurnal and nocturnal data to provide baseline data that address conservation and management objectives.